2019
DOI: 10.1055/a-1001-2154
|View full text |Cite
|
Sign up to set email alerts
|

Contrasting Role of Concentration in Rivaroxaban Induced Toxicity and Oxidative Stress in Isolated Kidney Mitochondria

Abstract: Rivaroxaban as a small molecule is able to directly and reversibly inhibit the factor Xa. This study was designed to figure out the evaluation effect of rivaroxaban on mitochondria obtained from rat kidneys. We isolated mitochondria from rat kidneys using gradient centrifugation. Then, the toxicity parameters including succinate dehydrogenase (SDH) activity, reactive oxygen species (ROS) formation, mitochondrial swelling, mitochondrial membrane potential (MMP) collapse and cytochrome c release were measured in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 31 publications
(58 reference statements)
0
11
0
Order By: Relevance
“…Each sample was measured using a fluorimeter set at 490 nm excitation and 520 nm emission wavelengths. The results were reported as %ΔΨm (the percentage of MMP) [24]. In this test, cumene hydroperoxide (a potent oxidizing agent EC50 = 120 µM [19]) was used as a negative control was used as a negative control 30 min after sofosbuvir (400 µM) addition.…”
Section: Investigation Of the Mitochondrial Membrane Potential (Mmp)mentioning
confidence: 99%
“…Each sample was measured using a fluorimeter set at 490 nm excitation and 520 nm emission wavelengths. The results were reported as %ΔΨm (the percentage of MMP) [24]. In this test, cumene hydroperoxide (a potent oxidizing agent EC50 = 120 µM [19]) was used as a negative control was used as a negative control 30 min after sofosbuvir (400 µM) addition.…”
Section: Investigation Of the Mitochondrial Membrane Potential (Mmp)mentioning
confidence: 99%
“…4 However, a more recent in vitro study, using rat kidney mitochondria, reported evidence of mitochondrial swelling and a collapse of the membrane potential following exposure to low doses of rivaroxaban. 5 The effect of apixaban, which is structurally related to rivaroxaban, has yet to be investigated on mitochondrial function. 6 Recent research supports not only an association between reduced cerebral mitochondrial function and neuropsychiatric symptoms and disorders, but also the aetiological role it may play.…”
Section: Discussionmentioning
confidence: 99%
“…4 However, a more recent in vitro study, using rat kidney mitochondria, reported evidence of mitochondrial swelling and a collapse of the membrane potential following exposure to low doses of rivaroxaban. 5 The effect of apixaban, which is structurally related to rivaroxaban, has yet to be investigated on mitochondrial function. 6…”
Section: Discussionmentioning
confidence: 99%
“…There is evidence that factor Xa has proinflammatory effects, therefore [65]. However, it has recently been shown to have protective effects against oxidative stress and mitochondrial toxicity [66]. Due to their chemical structure, sarilumab and fingolimod could have effects similar to CQ/HCQ in SARS-CoV-2.…”
Section: Discussionmentioning
confidence: 99%